Business model innovation for sustainable development: green technologies and BOP (Bottom of Pyramid) in emerging countries: South Africa and India - Gujral, Meenakshi (My University, 2017)
Globally, a vision exists of an economy which produces social, environmental and economic benefits, viz-a-viz three pillars of sustainable development, for all the individuals, communities and society at large. It also focuses on the development of the sustainable use of natural resources, to achieve a greater enviable society, therefore giving rise to the green economy (Bigg 2011). To make businesses sustainable, companies are increasingly focusing on green innovation, sustainable business solutions and re-inventing their business models, and expanding to untapped markets such as the bottom of the pyramid (BOP), consisting of more than four billion potential consumers (Farinelli, Bottini, Akkoyunlu & Aerni, 2011). Most research shows growth opportunities of green products in the bottom of pyramid (Olsen & Boxenbaum, 2009), and has increasingly created deliberations all over the world. Also, companies from both developed and developing countries are becoming increasingly interested in BOP. To successfully target the BOP with ‘green’ technologies, companies focus their business models on innovation, sustainability and economic profit, instead of gross margins (Prahalad & Hart, 2008). Very limited research evidence is present that links all these concepts together. And therefore, created an interest to examine how integration of green technology bring changes in business model innovation (BMI) for sustainability at BOP markets. The linkage between concepts - BMI, BOP and green technology, to bring sustainable development, has not been sufficiently explored, and especially with focus on emerging economies like South Africa and India. Therefore, the present research has three fold purposes. Firstly, to analyse and understand factors affecting the existing business models of various companies with green technologies targeting BOP markets for sustainable development. Secondly, the research brings an identification and understanding of number of key factors related to BMI, BOP markets and green technologies for sustainable development, and proposes a conceptual framework based on a series of underpinning relationships among these factors. Thirdly, it testifies the conceptualized theoretical framework on green business model innovation for sustainable development for BOP markets, among large companies. The primary objective of research study is to design a right green business model innovation across companies with green technologies for BOP markets. The secondary objective is to identify and compare the differences and similarities of green business model innovation for BOP markets of both South Africa and India. The present research undertakes a sequential exploratory mixed method approach, and is carried out in three phases: Phase 1: Exploration and study of business model innovation of identified industries/sectors with green technologies, targeting BOP segment for sustainable development, using qualitative research methods to formulate multiple cases. Phase 2: Identification of underpinning factors related to BMI, sustainable development and BOP consumers for green technologies; using qualitative methods and content analysis of results from phase 1, leading to design and development of theoretical framework of green business model innovation for South Africa and India. Phase 3: Testing of conceptualized framework of green business model innovation for sustainable development, using quantitative research methods. The present research tests underpinning factors of emerging green business model innovation for sustainable development, resulting from the qualitative phase, and is used to expand and generalize qualitative findings by using quantitative methods. The findings resulted in linking three theoretical emerging topics in the literature: business model innovation (BMI), green technology for sustainability and BOP. Four cases are developed through 33 face-to-face in-depth interviews with company top executives, using multiple case study approach. Each case comprised of sustainable business model innovation, representing comparison between South Africa and India, across four industries, namely, Energy, Banking, FMCG/Durable sectors and Cloud Computing. Qualitative content analysis and findings resulted in formation of themes and sub-themes and proposed prepositions, depicting the relationship between BMI, BOP, and green technology for sustainability. These prepositions aided in development of conceptual framework and proposed nine hypotheses. The conceptual model is quantitatively surveyed on 206 employees of large companies with focus on BOP markets. The quantitative findings supported all nine hypotheses. Therefore, indicating that integration of green technology is associated with performance of green product/service innovation and green process innovation in a company. Likewise, business model innovation variables; customer interface, infrastructure management and financial aspects, positively impacts sustainability of business model. The contribution of this thesis is in the development of green business model innovation for sustainable development, with focus on BOP markets. This adds to the contextual knowledge and empirical literature on business model innovation, green technologies and BOP markets. Theoretically, it brings better understanding of these concepts, and provides a basis of further research highlighting the importance of innovation while taking account of green economy and BOP. The findings provide marketing practitioners with better understanding of strategies that can be employed to innovate and change their own business models to incorporate green and sustainable initiative for BOP markets.
Doctoral research dissertation in the fulfilment of the requirements for the degree Doctor of Philosophy in Marketing at the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, South Africa, 2016
Keywords: Sustainable development--South Africa; Sustainable development--India; Management--Environmental aspects; Strategic planning--Environmental aspects